2014
DOI: 10.1021/jf501255w
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Combination of Dimethyl Disulfide and Dazomet as an Efficient Methyl Bromide Alternative for Cucumber Production in China

Abstract: The combination of dimethyl disulfide (DMDS) and dazomet (DZ) is a potential alternative to methyl bromide (MB) for soil disinfestation. The efficacy of DMDS plus DZ in controlling key soilborne pests was evaluated in a laboratory study and in two commercial cucumber greenhouses. Laboratory studies found that all of the combinations had positive synergistic effects on root-knot nematodes, two key soilborne fungi, and two major weed seeds. Greenhouse trials revealed that the combination of DMDS and DZ (30 + 25 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 26 publications
(37 reference statements)
1
31
0
Order By: Relevance
“…We found dimethyl-disulfide to be more effective using VIF than PE plastic mulch, which runs counter to the results shown by Gomez-Tenorio et al [54], who did not find any differences in the efficacy of dimethyl-disulfide in reducing Meloidogyne populations under VIF or PE plastic mulch, which was 100% effective when vermiculite was used as a substrate. Other authors found dimethyl-disulfide to be a less effective nematicide in natural soil than in artificial substrates [55,56]. Therefore, the type of soil/substrate seems to influence the results, and in soils where dimethyl-disulfide is not highly effective, using highly retentive plastic mulches can increase its efficacy in reducing RKN densities.…”
Section: Discussionmentioning
confidence: 99%
“…We found dimethyl-disulfide to be more effective using VIF than PE plastic mulch, which runs counter to the results shown by Gomez-Tenorio et al [54], who did not find any differences in the efficacy of dimethyl-disulfide in reducing Meloidogyne populations under VIF or PE plastic mulch, which was 100% effective when vermiculite was used as a substrate. Other authors found dimethyl-disulfide to be a less effective nematicide in natural soil than in artificial substrates [55,56]. Therefore, the type of soil/substrate seems to influence the results, and in soils where dimethyl-disulfide is not highly effective, using highly retentive plastic mulches can increase its efficacy in reducing RKN densities.…”
Section: Discussionmentioning
confidence: 99%
“…Metham sodium (MS), calcium cyanamide, abamectin and fosthiazate have been registered to control soil‐borne diseases in China. MS, dazomet (DZ), chloropicrin (CP), dimethyl disulfide (DMDS), 1,3‐dichloropropene (1,3‐D), sulfuryl fluoride (SF), and combinations of CP + MS, CP + DMDS, CP + 1,3‐D, DZ + 1,3‐D, DZ + DMDS, and CP + MS + 1,3‐D 14 have been registered and used commercially in China and other countries. As a comprehensive and versatile soil fumigation, MB has been used in diverse countries for >50 years to control fungi, bacteria, soil‐borne viruses, insects, mites, nematodes and rodents.…”
Section: Introductionmentioning
confidence: 99%
“…Diverse data on the various possible combinations of 1,3-D and Pic [ 8 15 ], MNa and Pic [ 12 ], 1,3-D and DZ [ 7 , 16 ], dimethyl disulfide (DMDS) and Pic [ 13 , 14 , 17 ], and DMDS and DZ [ 18 , 19 ] as chemical alternatives to MB have been published. Blends of 1,3-D and methyl isothiocyanate (MITC) in varying concentrations have previously been considered for use in Canada, Europe, and other countries [ 20 ].…”
Section: Introductionmentioning
confidence: 99%